Modeling with Math Trails - Druken, Bridget; Frazin, Sarah (Ohio Journal of School Mathematics, 2018)
The authors describe the application of a math trail activity used in a college classroom of future mathematics teachers to model with mathematics. In this activity, pre-service teachers select a location in their community, discover and design five trail heads, model situations using mathematical strategies learned in class, and share in a write-up or presentation. Insights about facilitating a math trail for mathematical modeling are provided, along with suggestions for teachers interested in using math trails in other contexts.